Small Enterprise Growth and the Rural Investment Climate : Evidence from Tanzania - Kinda, Tidiane; Loening, Josef L. (World Bank, Washington, DC, 2012)
This paper analyzes characteristics of nonfarm enterprises, their employment growth patterns, and constraints in doing business in rural Tanzania. Using unique survey data, the authors describe a low-return sector struggling to compete in a difficult business environment. However, about one-third of rural enterprises are growing fast. Most enterprises engage in agricultural trade. Due to a rapidly growing agricultural sector in recent years, limiting demand-side constraints, rural enterprise constraints in Tanzania mainly operate from the supply side. This suggests that, in particular, access to finance, road infrastructure, and rural cell phone communication is correlated with employment growth. A major finding is that subjective and objective measurements of business constraints are broadly comparable. The authors discuss a number of factors that would help to unleash the full potential of private sector-led growth in rural areas. The findings show that marginal improvements in the rural investment climate matter for growth.